Youth and Service Work in Fast Food Restaurants: Some Structural and Cultural Considerations - Bhatia, Anjali (Advances in Social Sciences Research Journal, 2024)
The India Employment Report (2024) highlights the problem of youth unemployment and its insufficient absorption in the non-farm sectors and recommends the skilling of youth as a remedy for tardy economic growth and employability. In view of the proposed solution, I suggest that we inquire into the nature and conditions of non-farm work in alternative sectors and the experience of this work for young people. The issue is the adequacy of training and skilling as sole measures to counter insufficient absorption. My concern regarding the recommended solution is a short shrift it gives to structural and cultural factors as facilitators or barriers to absorption, and the retention of workers. This article is an inquiry into the organization and culture of service work in fast food industry– a non-farm sector–under conditions of globalization. The experience of service workers reveals the relation between service work and attitudes towards cleaning, meaning of toilet cleaning, gendered division of labour, hierarchy of tasks, ascriptive and unequal access to jobs, and dignity of labour. The experience of service work is not the same for girls and boys; it is fraught with different sorts of tensions for them. These insights question the efficacy of training and skilling as the talismanic measures for countering the problems under consideration. They make a strong case for the consideration of cultural and structural realities of India.